A critical evaluation of inter-jurisdictional rules in the South African value-added tax system - Schneider, Ferdinand Dirk (Rhodes University, Faculty of Commerce, Department of Accounting, 2017)
This study analysed the current inter-jurisdictional rules in the South African Value-Added Tax (VAT) system, identified shortcomings, and proposed legislative amendments or additions to address these shortcomings. The research was conducted within an interpretative post positivism paradigm, applied a qualitative research methodology, and a doctrinal research method. A detailed review of the literature was conducted to establish the theoretical basis of a good tax system and the theory underpinning indirect and consumption taxation. The literature review also included an in-depth analysis of the South African VAT system and its treatment of resident and non-resident businesses with a South African physical or economic reach, and its treatment of local and cross-border transactions, including imported services. The literature review also considered the international VAT treatment of these transactions. To obtain a wider range of expert opinions regarding shortcomings in inter-jurisdictional rules in the South African VAT system, data was collected through structured interviews with South African and global VAT and indirect tax experts, using a questionnaire that was specifically designed for this purpose. This study proposed amendments and additions to the VAT Act, dealing with the VAT registration of non-resident suppliers; addressing various issues relating to the interjurisdictional VAT rate; proposing measures in connection with imported services; and legislating the intention of the legislator to tax final utilisation or consumption. The study finally recommended the introduction of a general place of supply rule linked to residency; specific place of supply rules for electronic, broadcasting, and telecommunication services; and zero rating provisions for electronic, broadcasting, and telecommunication services provided to non-resident suppliers by resident suppliers for services initiated outside South Africa.
Keywords: Uncatalogued